Application of expert system using certainty factor method to identify diseases in rice plants - Azmi, Isni; Gunawan, Gunawan; Anandianskha, Sawaviyya (Institute of Computer Science (IOCS), 2024)
This article explores the application of expert systems using certainty factor methods for disease identification in rice crops, highlighting the importance of information technology integration in agriculture. The study aims to develop a system that allows quick and accurate identification of rice disease, using certainty factor methods that are effective in dealing with data uncertainty. This study used a quantitative approach with a quasi-experimental design. The results indicate an effective system for identifying diseases, with significant implications for supporting farmers and improving food security. Suggestions for future research include system integration with mobile applications and real-time data analysis to improve system accessibility and applicability in modern agricultural practices.